PENGARUH PROMOSI MEDIA SOSIAL DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK UMKM KOTA TEBING TINGGI (STUDY KASUS PADA KERIPIK PISANG KEPOK KELING) - Dwi Zahrani; Fatimah Dinda Khairani; Rusmewahni; Imelda Mardayanti (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to determine the Influence of Social Media Promotion and Product Quality on the Purchase Decision of MSME Products in Tebing Tinggi City (Case Study on Kepok Keling Banana Chips). The analysis method used in this study is to use an instrument test, namely validity and reliability tests. Classic assumption tests, namely normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, determination coefficient analysis (R2), hypothesis tests, namely the T test and F test. The results of data processing in this study are Social Media Promotion Affects Purchasing Decisions, Product Quality Affects Purchasing Decisions, Social Media Promotion and Product Quality Affect Simultaneously (Simultaneously) Purchasing Decisions.